The Performance Of Wind Wing-Wall On Air Velocity For High-Rise Residential Building In Malaysia - Rosdi, Munirah (2018)
Global warming has sparked many to seek environmental friendly ways to reduce the impact of climate change especially in generating energy. The problem is as world population grows, demand and consumption of electricity increases. Population increase in South East Asian countries has compelled Malaysia, Singapore and Thailand to go for high rise buildings due to the limited land mass. Many did not realize that as living in high-rise buildings the endowment given by nature that the higher the buildings the faster the air velocity and this endowment was not taken into consideration during design process to tap the availability of natural ventilation. Present buildings are design using the conventional way of cooling the interior and that is by air-conditioning thereby increasing energy aggravated by the population increase. Several studies show that different architectural elements and techniques are related in improving the efficiency of ventilation systems in natural ventilated high-rise building. One of the latest methods in the field of construction is the use of wind wing-wall in high-rise building. Wind wing-wall is a solid panel, or a long standing wall alongside windows, balcony or other openings that can be used to redirect or guide air velocity into the building. Applying wind wing-walls is a method that encourages the natural wind ventilation into the building. Anyhow, limited studies have been carried out on the application of wind wing-walls by their effectiveness on overall indoor ventilation. Since Malaysia is mostly surrounded by seas and populations are mostly concentrated in the coastal area, the natural ventilation can be tapped for practical uses but information for empirical air velocity pattern seemed limited.